Plant-soil nitrogen, carbon and phosphorus content after the addition of biochar, bacterial inoculums and nitrogen fertilizer - Mikajlo, Irina; Pourrut, Bertrand; Louvel, Brice; Hynšt, Jaroslav; Záhora, Jaroslav (Taylor & Francis Inc., 2023)
The use of biochar in combination with mineral or biological amendments to improve its influence on soil-plant properties has received growing attention. The changes of nitrogen, carbon and phosphorus content in Lactuca sativa var. capitata aboveground plant biomass and soil after the addition of beech wood biochar combined with the addition of bacterial inoculums (Bacofil and Novarefm) and nitrogen fertilizer have been studied using spectrophotometry methods. Pots were filled with the arable soil from the plots in the protection zone of water sources (Březová nad Svitavou, South Moravia, Czech Republic). Biochar with inoculums decreased plant growth in the first yield of Novaferm treatment and both yields of Bactofil treatment. Increased plant biomass growth was observed with Novaferm addition in the second yield. Total nitrogen increase has been obtained in the plant aboveground biomass and soil of the treatments amended with inoculums and nitrogen fertilizer. The decrease of phosphorus content has been observed in plant aboveground biomass in the biochar amended samples.
Keywords: Biochar; carbon; inoculum; nitrogen; phosphorus; plant biomass; soil